2012
DOI: 10.1016/j.neurobiolaging.2011.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Ventral and dorsal visual streams in posterior cortical atrophy: A DT MRI study

Abstract: Using diffusion tensor magnetic resonance imaging tractography, ventral (inferior longitudinal fasciculus) and fronto-occipital (inferior fronto-occipital fasciculus) and dorsal (fronto-parietal superior longitudinal fasciculus) visual pathways were assessed in 7 patients with posterior cortical atrophy (PCA), showing either predominantly ventral or additional dorsal cognitive deficits. Corpus callosum and corticospinal tracts were also studied. Gray and white matter atrophy was assessed using voxel-based morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 87 publications
(108 reference statements)
10
43
1
1
Order By: Relevance
“…The most important finding of the present study is that WM damage was more severe and more widely distributed than expected on the basis of cortical atrophy and the cognitive profiles, particularly in the atypical AD forms in which cortical atrophy remains localized and the clinical symptoms relatively focal. Together with the few previous studies in which WM damage was assessed in separate series of EOAD (4,18), PCA (22)(23)(24), and lvPPA (19)(20)(21), our findings indicate that DT MR imaging may be able to demonstrate subtle abnormalities along WM pathways that link atrophic regions with still unaffected gray matter regions. More importantly, we found that DT MR imaging has the potential to allow assessment of the extensive disorganization of brain networks in focal AD, even before overt cognitive deficits become apparent.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The most important finding of the present study is that WM damage was more severe and more widely distributed than expected on the basis of cortical atrophy and the cognitive profiles, particularly in the atypical AD forms in which cortical atrophy remains localized and the clinical symptoms relatively focal. Together with the few previous studies in which WM damage was assessed in separate series of EOAD (4,18), PCA (22)(23)(24), and lvPPA (19)(20)(21), our findings indicate that DT MR imaging may be able to demonstrate subtle abnormalities along WM pathways that link atrophic regions with still unaffected gray matter regions. More importantly, we found that DT MR imaging has the potential to allow assessment of the extensive disorganization of brain networks in focal AD, even before overt cognitive deficits become apparent.…”
Section: Discussionsupporting
confidence: 75%
“…Despite the growing number of studies that show that severe microstructural abnormalities occur NEURORADIOLOGY: White Matter Degeneration in Atypical Alzheimer Disease Caso et al along WM tracts in late-onset AD besides the known loss of neurons in the gray matter, to date, a few DT MR imaging studies have demonstrated the WM network involvement in EOAD (4,18), lvPPA (19)(20)(21), and PCA (22)(23)(24). To our knowledge, no study has been conducted to compare the patterns of WM damage in EOAD, lvPPA, and PCA.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…In the present study, we focused on line bisection because in our experience other tests, such as target cancellation, are more likely to be contaminated by simultagnosia or object recognition deficits 17. As a consequence, line bisection was sometimes more likely to demonstrate signs of spatial bias in PCA than cancellation tests 18 19.…”
Section: Discussionmentioning
confidence: 95%
“…In early-onset AD, WM damage was found to be widespread and severer in the posterior fibers of the cingulum and CC compared to late-onset AD [16], while in PCA [65] and lvPPA patients [66,67] a prominent WM damage along visuospatial and language pathways, respectively, was found (fig. 2).…”
Section: Neuroimaging Studiesmentioning
confidence: 99%